A Technique to Facilitate the Native Valve Reimplantation During the David Procedure. Issue 4 (2nd March 2014) - El Arid, Jean‐Marc; Azzaoui, Richard; Koussa, Mohamed; Modine, Thomas
Abstract The reimplantation technique for valve‐sparing aortic root replacement is increasingly used to treat aortic root pathology. The systematic approach described by El Khoury in 2009 and modified in 2011 using the Valsava graft is simple and reproducible. However, in‐conduit suturing of the aortic valve annulus and small rim of sinus remnant to the graft sinuses is time‐consuming and may lead to bleeding or distortion of the prosthetic root. We describe a simple technique to facilitate the native valve reimplantation. doi: 10.1111/jocs.12311 (J Card Surg 2014;29:485–486)